Characteristics of exporting and non-exporting firms in Austria - Johannes Pöschl; Robert Stehrer; Roman Stöllinger (FIW - Research Centre International Economics, 2009)
In this study we provide detailed evidence on the importance and performance of exporters compared to non-exporters in Austrian manufacturing, based on firm level data. The results are in line with those found in other studies pointing towards the exceptional role of exporting firms with respect to various size and performance measures. We provide both descriptive as well as econometric evidence on these export premia' along these lines and further present a brief comparison with results found for other countries. Our findings however also suggest the existence of quite large differences across industries with respect to the export premia which deserves further attention.
Keywords: F10; D21; L60; 330; export premium; heterogenous firms; trade